Employment, turnover and career progress - Ferreira, Priscila (2016)
The severe economic downturn that followed the Global Financial Crisis of 2007 was accompanied by major fluctuations in the labour market. During the Great Recession the rate of job destruction was such that, by 2013, active population was at levels of 1999; employment levels were at an historical minimum; and the unemployment rate soared to 17,5%. This chapter inspects the dynamics behind the aggregate fl uctuations in the labour market and studies the determinants of mobility within (promotions) and between fi rms, and whether these have changed during crisis, using Portuguese (LEED) data. During crisis women became more likely to make between- rm moves with short gaps of unemployment and less likely to find a new job after a long gap or to make a job-to-non-employment transition. More educated workers are less likely to experience between fi rm job mobility, both before and during crisis, and became less likely to make job-to-non-employment transitions during crisis. Young workers are the group that most suffered from crisis: they became less likely to make job-to-job transitions and their hazard of experiencing a transition into unemployment shoot up.